Comparative Income of Independent Farmers and Plasma Farmers in Oil Palm Farming in Rural Areas, Central Mamuju District - Irmayani, Irmayani; Sampara, Nirwana; Arman, Arman; Rahmawaty, Rahmawaty; Rahbiah, Sitti; Masnur, Masnur (Agrikan Jurnal Agribisnis Perikanan, 2023)
This study aims to determine the Comparative Study of Palm Oil Farming Income of Independent Farmers and Plasma Farmers in Polongaan Village, Tobadak District, Central Mamuju Regency.The research method uses quantitative data with the help of Microsoft Excel 2010. The population collection in this study was carried out purposively, namely on oil palm farming by independent smallholders and plasma farmers. Meanwhile, the determination of the sample was carried out by purposive sampling as many as 30 oil palm farmers consisting of independent farmers and plasma farmers.The results of this study indicate that the income received by independent farmer farms is Rp. 40,245,000.00/month with an average income of Rp. 2,683,000.00. Meanwhile, plasma farmer farming is IDR 22,648,925 / month with an average income of IDR 1,509,928. From the difference in the income of oil palm farming of Rp. 17,596,075.00. farmers prefer to use an independent system because in plasma farmers income is done with a profit sharing system of 25% to farmers because the company covers everything from processing, breeding, fertilization